2011
DOI: 10.1038/ki.2011.57
|View full text |Cite
|
Sign up to set email alerts
|

Targeted reduction of advanced glycation improves renal function in obesity

Abstract: Obesity is highly prevalent in Western populations and is considered a risk factor for the development of renal impairment. Interventions that reduce the tissue burden of advanced glycation end-products (AGEs) have shown promise in stemming the progression of chronic disease. Here we tested if treatments that lower tissue AGE burden in patients and mice would improve obesity-related renal dysfunction. Overweight and obese individuals (body mass index (BMI) 26-39 kg/m(2)) were recruited to a randomized, crossov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(143 citation statements)
references
References 38 publications
8
125
0
1
Order By: Relevance
“…We and others have shown that plasma AGEs are related to adiposity [14,[73][74][75]. In the present study, we confirm these findings by showing the negative association between circulating levels of CML and various measures of adiposity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We and others have shown that plasma AGEs are related to adiposity [14,[73][74][75]. In the present study, we confirm these findings by showing the negative association between circulating levels of CML and various measures of adiposity.…”
Section: Discussionsupporting
confidence: 81%
“…We and others have demonstrated that the consumption of diets high in AGEs elicit deleterious effects throughout the body including: increased inflammation [14,15] driving insulin resistance [16] and impairing renal function [14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that the mechanisms contributing to the development of proteinuria also provoke AGE formation and accumulation, or that AGE exacerbate proteinuria. A role for AGE in the pathogenesis of proteinuria is suggested by a study that observed a significant reduction in albuminura after 2 weeks of a low AGE diet in 11 overweight and obese individuals (48).…”
Section: Egfr and Proteinuria As A Determinant Of Higher Safmentioning
confidence: 99%
“…These observations are important because factors such as diet and smoking are potentially modifiable. A recent study has reported a reduction in albuminuria and plasma levels of the proinflammatory cytokine monocyte chemotactic protein-1 in overweight and obese participants after just 2 weeks of a low-AGE diet (48).…”
Section: Other Determinants Of Saf In Ckdmentioning
confidence: 99%
“…A ingestão de substâncias formadas pela RM nos alimentos está correlacionada com o aumento de níveis séricos de AGEs em humanos URIBARRI et al, 2005;POULSEN et al, 2013), e, ensaios clínicos obtiveram benefícios com a restrição de PRM na dieta: tanto em pacientes com diabetes tipo 2 como em indivíduos saudáveis foram observados a diminuição do stress oxidativo, a diminuição de marcadores inflamatórios, melhora de marcadores da resistência a insulina e de disfunção vascular, e diminuição dos níveis séricos de AGEs (DELGADO-ANDRADE et al, 2007;URIBARRI et al, 2010;BIRLOUEZ-ARAGON et al, 2010;CHAO et al, 2010;HARCOURT et al, 2011).…”
Section: Lista De Tabelasunclassified